Theorems on the existence and nonexistence of solutions of the Cauchy problem for degenerate parabolic equations with nonlocal source - Afanaseva, N. V.; Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider the Cauchy problem for a doubly nonlinear degenerate parabolic equation with nonlocal source under the assumption that the initial function is integrable. We establish the existence and nonexistence of time-global solutions of the problem.